Tantangan dalam Integrasi Data Kesehatan dari Berbagai Sistem Electronic Health Record dalam Sistem Kesehatan Nasional - Suci Ariani; Resta Dwi Yuliani (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Electronic Health Records (EHRs) have become an important component in the digital transformation of the healthcare system in Indonesia. However, EHR implementation in many health facilities in Indonesia is still fragmentary and not fully integrated. The main challenges in integrating health data into the national health system are issues of interoperability, data security, and inter-institutional coordination. This study aims to identify and analyze the main challenges in integrating health data from various EHR systems into Indonesia's national health system and its impact on the quality of health services, operational efficiency, and data security. The research method used was a descriptive qualitative approach, which combined literature study and in-depth interviews with experts in the field of health information technology and health policy. A literature study was conducted to identify technical, operational, and policy challenges faced in EHR implementation in Indonesia. Expert interviews were used to validate the findings obtained from the literature and provide additional insights into the local context. Thematic analysis techniques were used to organize and interpret the data. The results showed that the lack of common data standards is a major obstacle in the integration of EHR systems in Indonesia.A total of 45% of healthcare facilities adopt HL7 standards, 30% adopt FHIR, and 25% use proprietary systems, leading to the inability to efficiently share data between institutions. In addition, data security issues are also a major concern, with many healthcare facilities yet to implement adequate security protocols. Limited coordination between health institutions also hinders wider integration. Nonetheless, EHR integration has the potential to improve operational efficiency, with up to 25% reduction in administrative time in institutions that have integrated their systems.